2019
DOI: 10.7717/peerj.7509
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of the VQ gene family in soybean (Glycine max)

Abstract: Background VQ proteins, the plant-specific transcription factors, are involved in plant development and multiple stresses; however, only few articles systematic reported the VQ genes in soybean. Methods In total, we identified 75 GmVQ genes, which were classified into 7 groups (I-VII). Conserved domain analysis indicated that VQ gene family members all contain the VQ domains. VQ genes from the same evolutionary branches of soybean shared si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
3
19
0
1
Order By: Relevance
“…In previous studies, the VQ family genes have been systematically analyzed in Arabidopsis [22], soybean [23], rice [37], banana [38], maize [39] and bamboo [40], and shown to play signi cant roles in regulating growth, development processes, and responding to biotic and abiotic stresses [2]. It is now important to complete a comprehensive analysis of the VQ gene family and to explore their evolution interactions in Gossypium spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the VQ family genes have been systematically analyzed in Arabidopsis [22], soybean [23], rice [37], banana [38], maize [39] and bamboo [40], and shown to play signi cant roles in regulating growth, development processes, and responding to biotic and abiotic stresses [2]. It is now important to complete a comprehensive analysis of the VQ gene family and to explore their evolution interactions in Gossypium spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the AtVQ08, AtVQ14, AtVQ17, AtVQ18 and AtVQ22 were identi ed as being involved in seed development, chloroplast development, and plant growth. On the other hand, a proportion of the GmVQ [23], PeVQ [40], VvVQ [44] and CsVQ [26] genes were also con rmed as being involved in regulating the growth at different tissues and different developmental stages. In this study, we also found that most GhVQ and GbVQ genes were differentially expressed in the different tissues, including ovule, ber, anther, leaf, root, sepal and stem, suggesting that the VQ genes also play an important role in cotton growth and development (Fig.…”
Section: Vq Genes Play Important Roles In Abiotic Stress Signaling Pamentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the VQ family genes have been systematically analyzed in Arabidopsis [24], soybean [25], sun ower [31], rice [26], banana [43], maize [27], bamboo [44], Cicer arietinum [32], Medicago truncatula [32], and tobacco [19], and has shown to play signi cant roles in regulating growth, development processes, and responding to biotic and abiotic stresses [2]. Here, we complete a comprehensive analysis of the VQ family genes and explore their evolutional mechanism in Gossypium species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to develop new cultivars with high resistance to biotic and abiotic stresses. ecently, VQ family genes have been identi ed at genome-wide levels in several plants, including Arabidopsis (34 VQs) [24], soybean (Glycine max) (74 VQs) [25], rice (39 VQs) [26], maize (Zea mays) (61 VQs) [27], Chinese cabbage (Brassica rapa spp. pekinensis) (57 VQs) [28], apple (49 VQs) [10], tea (Camellia sinensis) (25 VQs) [29], tomato (Solanum lycopersicum) (26 VQs) [30], sun ower (Helianthus annuus) (20 VQs) [31], tobacco (Nicotiana tabacum) (59 VQs) [19], Cicer arietinum (19 VQs) [32] and Medicago truncatula (32 VQs) [32].…”
Section: Introductionmentioning
confidence: 99%